Potential of Local Fruits (Kersen (Muntingia calabura), Kawista (Limonia acidissima) and Trembesi (Samanea saman) as Sweetener with Low Glycemic Index and Glycemic Load: Potensi Buah Lokal (Kersen (Muntingia calabura), Kawista (Limonia acidissima) dan Trembesi (Samanea saman) sebagai Bahan Pemanis dengan Indeks dan Beban Glikemik Rendah - Gemala Anjani; Dewi Marfu'ah Kurniawati; Ahmad Syauqy; Rachma Purwanti; Diana Nur Afifah; Tasya Safira Meliasari; Nur Faizah (Universitas Airlangga, 2023)
Diabetes is a metabolic disease that occurs in a person characterized by hyperglycemia. One of the cause of diabetes melitus is excessive consumption of simple sugar, so it is necessary to replace sugar (sucrose) with natural sweteeners derived from sweet fruit such as kersen, kawista and trembesi. This research is an experimental study to make natural sweeteners from kersen, kawista and trembesi fruit powder. The natural sweeteners of kersen, kawista dan trembesi fruit powder were analyzed for protein, fat, dietary fiber, ash, water, and carbohydrates. The solubility tests was carried out by the AOAC method, brix with refractometry, sugar content by spectrophotometry, organoleptic properties by hedonic test. The natural sweetener of trembesi fruit powder was analyzed glycemic index by the method of Wolever et al. (2001) and glycemic load was calculated from glycemic index test of food taking into account the amount of carbohydrates available in the serving size. There was a significant difference (p<0,05) in solubility, brix index, total sugar, sucrose content, organoleptic preference level moisture, ash, fat, protein, and carbohydrate content among the three types of fruit powder but there was no significant difference (p>0,05) on the dietary fiber and reducing sugar content. The glycemic index and glycemic load value of trembesi fruit powder were 29,09 and 7,09. Natural sweeteners from trembesi fruit powder has highest carbohydrate content compared to kersen and kawista fruit powder. Natural sweetener from trembesi fruit powder has low glycemic index (29,09) and glycemic load (7,09).